The Influence of Work Performance Assessment and Leadership Style on Employee Loyalty with Job Satisfaction as an Intervening Variable at PT. XYZ West Java Regional Head Office Bandung - Ramadhani, Fadhilah Dwiputri; Jaya, Rama Chandra; Natigor, Dayan Hakim; Karamang, Ezra; Muttaqin, Ridlwan (Dinasti Publisher, 2024)
This study aims to determine and explain the effect of work performance assessment and leadership style on employee loyalty with job satisfaction as an intervening variable (Case study at PT. XYZ West Java Regional Head Office Bandung). This research is a quantitative study with 53 employees as a population and uses non-probability sampling techniques, so the sample size uses the entire population. The data sources used are primary data and secondary data, then processed with the help of SPSS 26.0 for windows. The results showed that there was a significant influence of 78,4% of the work performance assessment variable and leadership style on job satisfaction. And also this study shows a significant influence of 93,4% of the job satisfaction variable in mediating work performance assessment and leadership style on employee loyalty.